Unique microRNA Signals in Plasma Exosomes from Pregnancies Complicated by Preeclampsia. Issue 3 (March 2020) - Li, Hui; Ouyang, Yingshi; Sadovsky, Elena; Parks, W. Tony; Chu, Tianjiao; Sadovsky, Yoel
Abstract : Although preeclampsia is a common and serious complication of pregnancy, insight into its pathobiology and diagnosis is lacking. Circulating plasma exosomes, which contain RNA and other molecules and have recently become accessible for diagnostics, may be informative in this regard. We tested the hypothesis that preeclampsia may affect the miRNA cargo within circulating maternal blood exosomes. We collected plasma from 60 pregnant women at term, including 20 women with pregnancy complicated by preeclampsia, and 20 women with fetal growth restriction and 20 with healthy pregnancy, serving as controls. We isolated exosomes from the maternal plasma by continuous density gradient ultracentrifugation. Our main outcome variable was exosomal miRNA cargo, analyzed by quantitative polymerase chain reaction-based TaqMan advanced miRNA assay in a card format and the expression of differentially expressed exosomal miRNA in whole plasma from the same participants. We found that 7 miRNA species were differentially expressed in exosomes from women with preeclampsia and those from controls. In contrast, there was no significant difference in exosomal miRNA expression between women with fetal growth restriction and controls. The results were not affected by fetal sex. Only one of the preeclampsia-related, differentially expressed exosomal miRNAs was significantly different in whole plasma miRNA analysis. We concluded that unlike whole plasma miRNA, exosomes extracted from the plasma of women with preeclampsia exhibit a unique miRNA profile, suggesting that plasma exosomal miRNA could provide insight into the pathophysiology of preeclampsia, and may play a role in disease diagnostics. Abstract : Supplemental Digital Content is available in the text.